2015
DOI: 10.4102/phcfm.v7i1.776
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of doctors to a clinical guideline for hypertension in Bojanala district, North-West Province, South Africa

Abstract: BackgroundClinical guidelines are systematically developed statements that assist practitioners and patients to make healthcare decisions for specific clinical circumstances. Non-adherence of doctors to guidelines is thought to contribute significantly to poor delivery of clinical care, resulting in poor clinical outcomes.AimTo investigate adherence of doctors in rural district hospitals to clinical guidelines using the South African Hypertension Guideline 2006 as an example.SettingFour district hospitals in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 13 publications
5
44
3
Order By: Relevance
“…Besides clinical variables, the potential influence of physician preference and degree of familiarity with/attitude toward ESC guidelines, which promote use of FDCs over free‐dose combinations, cannot be overlooked . For example, previous studies have associated older practitioner age with poorer adherence to guidelines on the management of hypertension . Furthermore, the disparity between prescription behaviors in what were formerly Eastern and Western Germany may also be related to physician factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides clinical variables, the potential influence of physician preference and degree of familiarity with/attitude toward ESC guidelines, which promote use of FDCs over free‐dose combinations, cannot be overlooked . For example, previous studies have associated older practitioner age with poorer adherence to guidelines on the management of hypertension . Furthermore, the disparity between prescription behaviors in what were formerly Eastern and Western Germany may also be related to physician factors.…”
Section: Discussionmentioning
confidence: 99%
“…7 For example, previous studies have associated older practitioner age with poorer adherence to guidelines on the management of hypertension. 18 Furthermore, the disparity between prescription behaviors in what were formerly Eastern and Western Germany may also be related to physician factors. Evidence suggests that in the east, the average age of practitioners is lower and hypertension is more prevalent 19,20 ; thus, it may be speculated that doctors in the east refer and adhere to guidelines more often.…”
Section: Factorsassociatedwiththeprescriptionofan Fdcratherthanafrementioning
confidence: 99%
“…One important aspect that has not been well studied is that of the age of practitioners. There has been a change in practice over the generations with those clinicians in the second half of their careers practising as individuals according to their experience and knowledge whereas the younger generations are practising in a more collaborative team-based medicine which is more strongly influenced by protocols and guidelines [10].…”
Section: Not All Physicians Follow Guidelinesmentioning
confidence: 99%
“…Non-adherence of doctors to guidelines is thought to contribute significantly to poor delivery of clinical care, resulting in poor clinical outcomes. 11 In a study done in the Bojanala district of South Africa overall adherence of doctors to treatment guidelines for hypertension was found to be low (51.9%). 20 Similar to the finding in the current study, the Bojanala study also found that the low adherence rates were related to age (older doctors) and the rates of adherence also differed with regard to various aspects of the guidelines.…”
Section: Adherence Practices To the Sti Guidelinesmentioning
confidence: 99%
“…10 There is also evidence that doctors do not always adhere to national treatment guidelines. 11 This study sought to determine the knowledge, attitudes and practices of doctors regarding syndromic STI management guidelines at Jubilee Hospital.…”
Section: Introductionmentioning
confidence: 99%